Oncoplastic Breast Reduction: Maximizing Aesthetics and Surgical Margins. (13th November 2012) - Chang, Michelle Milee; Huston, Tara; Ascherman, Jeffrey; Rohde, Christine
Abstract : Oncoplastic breast reduction combines oncologically sound concepts of cancer removal with aesthetically maximized approaches for breast reduction. Numerous incision patterns and types of pedicles can be used for purposes of oncoplastic reduction, each tailored for size and location of tumor. A team approach between reconstructive and breast surgeons produces positive long-term oncologic results as well as satisfactory cosmetic and functional outcomes, rendering oncoplastic breast reduction a favorable treatment option for certain patients with breast cancer.